2021
DOI: 10.1007/s00395-021-00900-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Na+ and Ca2+ mishandling drives vicious cycle involving CaMKII, ROS, and ryanodine receptors

Abstract: Cardiomyocyte Na+ and Ca2+ mishandling, upregulated Ca2+/calmodulin-dependent kinase II (CaMKII), and increased reactive oxygen species (ROS) are characteristics of various heart diseases, including heart failure (HF), long QT (LQT) syndrome, and catecholaminergic polymorphic ventricular tachycardia (CPVT). These changes may form a vicious cycle of positive feedback to promote cardiac dysfunction and arrhythmias. In HF rabbit cardiomyocytes investigated in this study, the inhibition of CaMKII, late Na+ current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Abnormally high RyR2 channel activity has a central role in contractile deficiency and arrhythmogenesis underlying sudden cardiac death 3,4,49 and posttranslational modifications of the channel including PKA/CaMKII-mediated phosphorylation or oxidation are involved, as well as their interplay (ie, ROS-CaMKII-RyR2) at the cytosolic face of RyR2. 5,50 Here, we show a novel regulatory axis for RyR2 ROS modulation involving the luminal ROS sensor Ero1α and the luminal RyR2-binding protein ERp44. Our previous studies showed that β-adrenergic stimulation induces Ca 2+ -dependent VT/VF in 100% of ex vivo hearts from rats with pressure-overload induced hypertrophy.…”
Section: Ero1α Upregulation Promotes Proarrhythmic Spontaneous Sr Ca ...mentioning
confidence: 88%
“…Abnormally high RyR2 channel activity has a central role in contractile deficiency and arrhythmogenesis underlying sudden cardiac death 3,4,49 and posttranslational modifications of the channel including PKA/CaMKII-mediated phosphorylation or oxidation are involved, as well as their interplay (ie, ROS-CaMKII-RyR2) at the cytosolic face of RyR2. 5,50 Here, we show a novel regulatory axis for RyR2 ROS modulation involving the luminal ROS sensor Ero1α and the luminal RyR2-binding protein ERp44. Our previous studies showed that β-adrenergic stimulation induces Ca 2+ -dependent VT/VF in 100% of ex vivo hearts from rats with pressure-overload induced hypertrophy.…”
Section: Ero1α Upregulation Promotes Proarrhythmic Spontaneous Sr Ca ...mentioning
confidence: 88%
“…Numerous other factors can contribute to arrhythmogenesis. Altered myocyte Ca 2+ handling and enhanced (CaMKII‐dependent) SR Ca 2+ leak are characteristic of HF, 61 which can increase APD alternans and afterdepolarizations. 47 , 48 , 49 , 50 Importantly, DADs were reduced post‐TAC in PKD1 cKO (Figure 8 ) in line with reduced cellular hypertrophy and larger I K1 density (Figures 4 and Figure S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further explain the association between various sarcomere mutations and ion channel remodeling in experimental models, the potential mechanistic connections point to the critical calcium regulatory protein calcium calmodulin-dependent protein kinase II (CaMKII), which was proved to bridge the gap between gene variants and arrhythmogenic ion channelchanges ( 39 ). The autophosphorylation of CaMKII enhances its activity on downstream targets such as the phosphorylation of LTCC β-subunits, slowing down current inactivation and prolonging the entry of Ca2+ during systole ( 40 ). The phosphorylation of the Na+ channel (Nav1.5) changed the inactivation of INa, increasing INaL.…”
Section: Cellular Mechanism Of Ventricular Arrhythmias In Early-stage...mentioning
confidence: 99%
“…Increased INaL leads to APD prolongation, which increases the possibility of EAD and DAD, promoting calcium influx at the plateau phase, further aggravating calcium overload, and predisposing patients to arrhythmic diastolic dysfunction. INaL inhibitors shorten the APD and reduce calcium overload ( 20 , 40 ). It was also proved in cardiomyocytes isolated from septal myectomies of HCM patients as INaL inhibitor Ranolazine showed beneficial effects by lowering intracellular Ca2+ levels ( 24 ).…”
Section: Drugs Against Ventricular Arrhythmia In Hcmmentioning
confidence: 99%